An Analysis of Romanian President Klaus Werner Iohannis's Political Communication Attributions to Gain Populist Support (a Case Study of Romania's Membership in the European Union) - Bambang Prihartadi; T Titi Widaningsih; Heri Budianto; Prasetya Yoga Santoso; Dewi Widowati (Syntax Corporation Indonesia, 2025)
Romanian President Klaus Werner Iohannis (KWI) was president for the first term from 2014 to 2019 and for the second term from 2019 to 2025. During his time in office, some populist groups in Romania said that joining the European Union (EU) brought economic problems, foreign culture, unhappiness with government, feeling like they lost rights, being unhappy with the EU, and worrying about losing control over their country. This kind of populism happened not only in Romania but also in other EU countries. The goal of this research is to understand what populism means, how people think about it, and how President KWI tried to get support from these populist groups while Romania was part of the EU. This study uses a mix of Heider's attribution theory and Dan Nimmo's political communication ideas. The study guesses that even though some groups were against the EU or Euroscepticism, by using political communication strategies, President KWI could deal with these issues and keep Romania in the EU. The results showed that populist groups kept pushing for anti-EU, anti-elites, anti-establishment, and anti-pluralism ideas to win public support. The public had mixed feelings about these campaigns. By the end of KWI's time in office, more people started to support populists because they lost trust in the government, which wasn't strong enough in fighting corruption. Still, by using political communication strategies, Romania stayed in the EU and joined the Schengen Area on January 1, 2025. Also, President KWI was able to serve two terms.